Islamic banking: Operation and instruments - Mohamed Naim, Asmadi; Zainol, Zairani (UUM Press, 2015)
Since the first modern Islamic savings bank was established in the Egyptian town of Mit Ghamr during the 1960s, and the establishment of Hajj investment fund in Malaysia also in the late 1960s, the Islamic financial system has continued to grow rapidly.Although Islamic banking is the most developed part of Islamic finance, the expansion of the Islamic capital market, encompassing the equity and debt markets, as well as the Islamic money market, cannot be ignored. Despite its rapid expansion, the Islamic financial system is still poorly understood by the Muslim world and continues to be puzzling to most Westerners.The sophisticated and innovative products and services that have been developed in the Islamic financial market are usually perceived as similar to their conventional counterparts; however these products/services are very different in terms of their modus operandi and principles. The Arabic terms associated with products/services are considered jargon to most people.Thus, the need to understand Islamic banking system and to foster an interest in Islamic finances, specifically Islamic banking, have resulted in the writing of this book. This book aims to share this knowledge with readers who are interested in understanding Islamic banking operations and its products and services. It is also hoped that this book will provide assistance to its readers to understand certain aspects of Islamic banking operations and services though the book does not mean to cover comprehensively those topics.This book covers Islamic banking operations by providing an overview about the balance sheets of conventional and Islamic banks.The reader is then exposed to Islamic banking products, both in deposits and financing activities.In the final part of this book, the reader is familiarized with Islamic trade finance products and instruments. We would like to express our highest gratitude and deep appreciation for the assistance and support provided by few individuals and institutions. Among others, the International Shariah Research Academy (ISRA), for providing initial insights; the Islamic Banking and Finance Institute of Malaysia (IBFIM) for providing valuable inputs; and Universiti Utara Malaysia for continuously supports the writers’ efforts to contribute knowledge to the society academically.Hopefully, this book will benefit practitioners, academics, students, the public and those who aspire to follow the development of the Islamic finance industry and its sciences.